Influence of ascending aortic dilation in patients undergoing transcatheter aortic valve replacement: A multicenter, retrospective studyCentral MessagePerspective - Kang An, MD; Fengwen Zhang, MD; Wenbin Ouyang, MD; Yu Han, MD; Da Zhu, MD; Xiangbin Pan, MD (JTCVS Structural and Endovascular)
Objective: The influence of dilated ascending aorta (AA) in patients undergoing transcatheter aortic valve replacement (TAVR) remains unclear. The aim of the present study was to evaluate the safety and efficacy of TAVR in patients with dilated AA. Methods: We identified 601 patients who underwent transfemoral TAVR and had baseline contrast computed tomography available for AA evaluation. Results: Two hundred sixty-nine individuals (44.8%) had baseline AA diameter ≥40 mm. The probabilities of 3-year all-cause mortality were 11.9%, 7.4%, 12.1%, and 16.8% at the baseline AA diameters of <40, 40 to 44, 45 to 49, and ≥50 mm, respectively. No statistical significances were found between the groups. Only 1 patient with baseline AA diameter of 39 mm experienced type A aortic dissection 10 months after the procedure. No other adverse aortic events were observed. A positive correlation between baseline AA diameter and aortic expansion rate was found in patients with bicuspid aortic valve. However, the aortic expansion rates in patients with tricuspid aortic valve appeared to remain stable across the baseline AA diameters. Conclusions: The presence of AA dilation did not increase the overall mortality in a TAVR population. The incidence of adverse aortic events was low. However, the efficacy of TAVR in patients with bicuspid aortic valve and AA dilation requires further study.